High Temperature Performance Data Analysis and Evaluation of Quartz Crystal Resonators - Jia Liu (The International Journal of Multiphysics, 2024)
In recent years, with the continuous advancement of science and technology, quartz crystals have been playing an increasingly significant role in various fields. Particularly in the realms of computing and electronics, quartz crystals, as vital oscillatory components, have garnered considerable attention due to their stability and performance. This study used computer modeling simulation to investigate the vibration state of AT-cut quartz crystal resonators under different temperature conditions. Using the incremental thermal field equations, we established a mathematical model that correlates the elastic constants, piezoelectric coefficients, and dielectric constants with temperature. Using COMSOL Multiphysics finite element simulation software, we analyzed the displacement distribution in the X-direction of AT-cut quartz crystals under free vibration conditions at various temperatures. Additionally, the study examined the displacement distribution of spurious modes in the Y and Z directions. Subsequently, we introduced an energy distribution formula to calculate the energy proportion within the electrode area at different temperatures. The computer simulation data results show that with the increase of temperature, the surface displacement of the quartz crystal shows a typical energy capture phenomenon. Despite a slight decrease in energy proportion within the electrode area, the reduction is minimal, ensuring robust thickness shear vibration mode maintenance. This suggests that quartz crystals exhibit strong thermal stability in high-temperature environments, making them suitable as sensitive elements in Quartz Crystal Microbalance (QCM) sensors under such conditions.